Economic body robustness evaluation algorithm - LING HONGTAO (2023)
The invention provides an economic body robustness evaluation algorithm, which comprises the following steps: regarding an economic body as an ecological system, and constructing an economic body robustness calculation formula according to four indexes: robustness = diversity + stability + vitality + balance; wherein n is the number of subject types in the economics, and the subject types are results obtained by performing natural clustering on subjects by using a Kmeans algorithm according to net profit, organization degree and net assets of the subjects; the avgTime is the average survival time of the main body in the economic body, and the avgProfit is the average net profit of the main body in the economic body; newNum is the new number of the main bodies in the economic body, and Num is the existing number of the main bodies in the economic body; the Kurtosis is the kurtosis of the number distribution of each main body type in the economic body, and the Skewness is the skewness of the number distribution